Formulasi Strategi Peningkatan Kompetensi Petani melalui Program “Temu Bisnis Tani” di Kabupaten Sukabumi dengan Analisis Swot - Riyan Mirdan Faris; Muhammad Dzikri Alfajrin; Intan Deanida Pratiwi; Kalfajrin Kurniaji; Mulus Wijaya Kusuma (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to formulate strategic recommendations for improving farmers’ competencies in Sukabumi Regency through the implementation of the Temu Bisnis Tani (Farm Business Meeting) Program using a SWOT analysis approach. The research was motivated by the low quality of human resources in the agricultural sector, particularly in terms of technical skills, managerial capabilities, entrepreneurship, and digital literacy. The Temu Bisnis Tani Program serves as a strategic platform to strengthen collaboration between farmers and agribusiness actors, expand market networks, and facilitate knowledge transfer. A descriptive qualitative method was employed, involving in-depth interviews, field observations, and document analysis, which were integrated into IFAS and EFAS matrices to determine the program’s strategic position. The results indicate that the IFAS score (3.48) and EFAS score (3.10) place the program in Quadrant I (SO strategy – aggressive), demonstrating strong internal capabilities and significant external opportunities. Recommended strategies include increasing the frequency and scope of Temu Bisnis Tani activities, integrating digital agriculture technologies, strengthening farmer group institutions, and expanding partnerships with private sector stakeholders. The study concludes that enhancing farmers’ competencies requires not only technical interventions but also managerial development, entrepreneurial capacity building, and improved market access to support a productive, adaptive, and sustainable agricultural system.